High-frequency log-domain current-mode multiphase sinusoidal oscillator - Prommee, P.; Sra-ium, N.; Dejhan, K. (My University, 2010)
This study describes the design of a multiphase sinusoidal oscillator (MSO) based on log-domain filtering concept. The circuit is a direct realisation of a first-order differential equation for obtaining the inverting and non-inverting low-pass filters. Each low-pass filter comprises only a grounded capacitor and four transistors. The proposed MSO can be instantaneously controlled over a very wide frequency range by controlling the current for the oscillation frequency and oscillation condition which indicates the proposed MSO's suitability in high-frequency applications. A validated bipolar junction transistor (BJT) model is used in SPICE simulation operated from a single power supply as low as 2.5 V. The oscillation frequency is controlled over four decades of frequency. The total harmonic distortions for three phase (11.5 MHz) and four phase (7 MHz) are, respectively, obtained around 2.4 and 2.2% which enables them to be fully integrated in telecommunication systems. The power consumption is around 5.5 mW for 100 μA bias current. Moreover, experimental results of three-phase MSO are included. © 2010 The Institution of Engineering and Technology.